Quantitative ethnobotanical evaluation of medicinal plants in District Karak, KP, Pakistan - Sultana, Asia; Rahim, Zubia; Qasim, Muhammad; Saleem Khan, Muhammad; Ali, Maroof; Rahim, Muhammad Asif Rahim; Hussain, Muhammad Zahid; Shazia Dilbar , Shazia Dilbar (Ethnobotany Research and Applications, 2025)
Background: The opulent vegetation of District Karak, boasting an array and exotic medicinal plants is still unexplored. This study focused on the ethnomedicinal knowledge of uncharted sites of District Karak. Medicinal plants help to identify pharmacognostically potent species. This study will help in drug discovery. Methods: Field surveys based on semi-structured interviews were conducted with local informants and healers (a total of 100) to document the ethnomedicinal uses of plants. To evaluate the ethnomedicinal data various quantitative indices frequency citation (FC), relative frequency citation (RFC), fidelity level (FL), use value (UV), informant consensus factor (FIC), Jaccard index (JI) and relative importance level (RIL) were targeted to document the data. Results: A total of 52 plant species belonging to 31 families were identified which were used for various purposes. The most commonly used plant species were B. campestris, D. sissoo, S. arundinaceum, Z. jujuba, Z. nummularia, D. viscosa, S. mascatense S. suretenses, T. Angustata, V. negundo, F. cretica, H. controtus, J. maritimus, C. edulis Edgey, W. coagulana, A. adscendens and C. dactylon etc. The categories of the informants, plant life form, part used, mode of preparation, rout of uses and ethnomedicinal uses were recorded. The highest RFC value was found for Ziziphus jujuba (0.15) followed by Z. nummularia (0.13), A. vera (0.09), P. dactyliferous (0.09), and E. austrails (0.07), M. arvensis (0.06) respectively. Z. jujuba was the most used medicinal plant species with the highest use value (0.18). The reported ailments were classified into 17 disease categories based on ICF values. The highest number of plant species was identified to treat kidney-related ailments (2.25). M. longifolia showed the maximum FL (89%), used against dermatitis disorders. The maximum Jaccard’s similarity index (JSI) showed that Jandrai and Toor mirch had the highest similarity followed by Toor mirch and Turkha koi with JSI of (37.14%), (19.51%) and respectively. Since the three villages were part of the same ethnic and religious group they showed significant variances in traditional ecological knowledge, which might be explained by socioeconomic differences and variability in the local environment. Conclusion: The current study highlights the significance of traditional knowledge of ethnomedicinal plants in selected areas. The study suggested that these plant species have the potential to contribute to the development of new drugs and therapies emphasizing the need for future research and conservation reports. Keywords: Ethnomedicinal, quantitative indices, informant consensus, Jaccard’s similarity index, fidelity level, relative frequency citation, indigenous.